2010
DOI: 10.1177/0020764010374417
|View full text |Cite
|
Sign up to set email alerts
|

A substantive theory of recovery from the effects of severe persistent mental illness

Abstract: Recovery can occur in any one or all of the three dimensions and thus can be complete or partial. It is important to ask, therefore: recovery from what, recovery of what, and recovery to what?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…The unpredictability of outcomes, with or without treatment, suggests that finding simple associations between these factors may be difficult. It may be that approaches which use multiple sources to define a multi-faceted approach to defining recovery are needed and this fits with qualitative research which showed that recovery could occur in three domains (biomedical, psychological and social) and could be complete or partial (Henderson, 2010). The evidence base indicates that clinical and recovery measures assess different aspects of outcome.…”
Section: Introductionmentioning
confidence: 91%
“…The unpredictability of outcomes, with or without treatment, suggests that finding simple associations between these factors may be difficult. It may be that approaches which use multiple sources to define a multi-faceted approach to defining recovery are needed and this fits with qualitative research which showed that recovery could occur in three domains (biomedical, psychological and social) and could be complete or partial (Henderson, 2010). The evidence base indicates that clinical and recovery measures assess different aspects of outcome.…”
Section: Introductionmentioning
confidence: 91%
“…in social networks, and that a greater loss of activities had a negative influence on well-being (16). More broadly, it is widely acknowledged that people with a mental illness may experience a profound degree of loss (7,8,(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study of first-episode patients in recovery from bipolar disorder reported that 98% of the sample achieved syndromal recovery, defined as no longer meeting the diagnostic criteria of the illness within 2 years, compared to only 38% achieving functional recovery, or regaining the life roles they had enjoyed prior to the onset of illness (Tohen et al 2000). Concepts or models of recovery are diverse (Davidson et al 2010); Henderson 2010; Jacobson and Greenley 2001; Starnino 2009). A good example is the integrated sociological model of recovery which postulates that demographic factors (such as age and gender) and social roles are associated with the onset of mental illness, and being able to recognize the symptoms and cope with stigma will have positive consequences for general well-being (Ralph and Corrigan 2005).…”
Section: Introductionmentioning
confidence: 99%